Erythrocyte Glutathione Concentrations and Fleece Traits in Karayaka and Crossbred Bafra Sheep - Akdaǧ, F.; Serter, M.; Meral, Y.; Çakiroǧlu, D. (Ecole Nationale Vétérinaire Toulouse, 2011)
This study was aimed to investigate the relationships between erythrocyte glutathione (GSH) concentrations and fleece characteristics and yields in Karayaka and Chios x Karayaka crossbred (Bafra) sheep. For that, the GSH contents in erythrocytes and the fleece traits (fleece yield, greasy and clean fleece weights, uniformity, staple length, tenacity, fibre diameter and washing yield) were determined in 30 Karayaka and 30 Bafra sheep, 1-4 years old, before and after shearing. Firstly, shearing has induced a significant positive effect on the erythrocyte GSH contents, secondly, slightly but not significantly higher erythrocyte GSH contents, as well as significant higher staple length, fleece yields, greasy and clean fleece weights were recorded in the Karayaka sheep than in the Bafra sheep and thirdly a significant and positive correlation was evidenced between the biochemical parameter and the fleece yield. These results suggest that the erythrocyte GSH content would be considered as a marker of high fleece production in sheep.
Keywords: Crossbred; Fleece; Fleece Yield; Glutathione; Karayaka; Sheep; Staple Length